A sustained release of tablet granules associated with ZnS nanocrystals using Tamarind seed polysaccharide - Karthikeyan Ganesan, Shyam Kumar Rajaram, Arunachalam Chinnathambi, Veerlakshmi Murugesan, Kasturiprabha Muruganantham, Thoufik Rahuman Amanullah, Infant Santhose Barthelomai, Sathishkumar Chinnasamy (Journal of Applied Pharmaceutical Science, 2013)
Tamarind seed polysaccharide (TSP) isolated from tamarind kernel powder was investigated for sustained release manners of salicylic acid drug. Tablet granules of salicylic acid were prepared, with two different grades of TSP and Cross linked TSP and embedded with chemically synthesized ZnS nanocrystals. Five different formulations made and the drug excipient mixtures were subjected to pre-formulation studies such as physicochemical studies, in vitro dissolution test, disintegration test, angle of repose and drug content. The physicochemical properties of tablets were found within the limits. Formulation F1 and F5 containing TSP and Cross linked were found to release the drug in sustained manner up to 24 hour and were stable under accelerated conditions of temperature for 6 months since there were no significant changes in drug content and physical parameters. This formulation was more comfortable to the user due to less erosion, faster and optimum pH of surrounding medium.
Keywords: Tamarind kernel powder, Tamarind Seed Polysaccharide